2017
DOI: 10.1158/0008-5472.can-17-0498
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Catabolism in Liver Tumors Induced by c-MYC Can Be Sustained by Various PKM1/PKM2 Ratios and Pyruvate Kinase Activities

Abstract: Different pyruvate kinase isoforms are expressed in a tissue-specific manner, with pyruvate kinase M2 (PKM2) suggested to be the predominant isoform in proliferating cells and cancer cells. Due to differential regulation of enzymatic activities, PKM2 but not PKM1 has been thought to favor cell proliferation. However, the role of PKM2 in tumorigenesis has been recently challenged. Here we report that increased glucose catabolism through glycolysis and increased pyruvate kinase activity in c-MYC-driven liver tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 49 publications
4
63
0
Order By: Relevance
“…1b). These results suggested that glucose catabolism through glycolysis and catabolism of both glucose and glutamine through the Krebs cycle are increased on MYC-induced liver tumours in comparison with normal tissue counterparts consistent with our previously published results 10,12 .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1b). These results suggested that glucose catabolism through glycolysis and catabolism of both glucose and glutamine through the Krebs cycle are increased on MYC-induced liver tumours in comparison with normal tissue counterparts consistent with our previously published results 10,12 .…”
Section: Resultssupporting
confidence: 92%
“…2c). To induce MYCdriven tumours in this case we used hydrodinamics-based transfection of a MYC-encoding plasmid 12,27 . Since ectopic expression of Cre recombinase has been previously shown to exacerbate MYC-induced apoptosis and reduce the efficiency of MYC-induced tumourigenesis 28 , we also combined the ectopic expression of MYC with the expression of MCL1, another gene frequently overexpressed in human liver tumours (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…c‐Myc is an important member of the Myc gene family and is involved in the development of various tumors. It plays an important role in tumor energy metabolism, regulates glycolysis, and promotes the Warburg effect in tumor . Pyruvate kinase is a key enzyme in the last step of glycolysis that transfers a phosphate group from phosphoenolpyruvate to ADP, resulting in the formation of pyruvate and an ATP molecule .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the ratio between PKM1 and PKM2 isoforms plays a key role in cancer progression 34-38 . In our study, we found PKM1 is not stronglyassociated with the survival of cancer patients as it has been reported 18 .…”
Section: Discussionmentioning
confidence: 99%